Circadian Oscillations of Minimal Erythema Dose (MED) are Also Influenced by Diet in Patients with Psoriasis: A Chronomedical Study - Giovanni Damiani; Alessia Pacifico; Egeria Scoditti; Sara di Gregorio; Massimo Del Fabbro; Claudia Cozzolino; Alessandra Buja; Santo R. Mercuri; Vittoria G. Bianchi; Ayman Grada; Sergio Garbarino; Christopher G. Bunick (Adis, Springer Healthcare, 2023)
Abstract Introduction Minimal erythema dose (MED) remains a parameter of paramount importance to orient narrow-band (NB)-UVB phototherapy in psoriatic (PsO) patients. Recently, circadian rhythm and diet were recognized as potential MED modulators, but their mutual interaction remains understudied. Thus, we aimed to evaluate the potential diet modulation of MED circadian oscillations. Methods In the first phase, a cohort study was performed comparing potential MED oscillations (morning, afternoon, and evening) among omnivorous psoriatic patients before and after a phototherapy cycle and omnivorous healthy controls. The two groups were age-, gender-, skin-type-, MED-, and diet-matched. Then, in the second phase, another cohort study was carried out comparing MED oscillations 24 h after the last phototherapeutic session only in psoriatic patients cleared with NB-UVB and undergoing different diets (vegan, vegetarian, paleo , ketogenic, intermittent circadian fasting, and omnivore). Patients with different diets were age-, gender-, and skin-type matched. Results In the first phase, we enrolled only omnivores, specifically 54 PsO patients and 54 healthy individuals. Their MED before and after NB-UVB therapy changed significantly among the three different time-points (morning, afternoon, and evening) (p < 0.001). The time effect was statistically significant in both groups before and after phototherapy. In the second phase, we enrolled 144 PsO patients (vegan, vegetarian, paleo, ketogenic, intermittent circadian fasting, and omnivore). MED circadian oscillations preserved a significant difference also after clearance and were influenced by diet type and time of day (p < 0.001). In particular, vegans displayed the lowest MED values, whilst Ramadan fasting showed the highest values in morning, afternoon, and evening. Conclusions Diet, like other ongoing therapies, should be reported in the medical records of patients with psoriasis undergoing NB-UVB and patients with lower MEDs should be preferentially treated in the morning when the MED is higher.